Synodale Prozesse in der katholischen Kirche - Rees, Wilhelm; Müller, Ludger (innsbruck university press, 2016)
One of the goals of the Second Vatican Council (1962-1965) was to revive the synodal structures in the Church, which had played an important role throughout history. As a result of this Council, synods have been held both in individual dioceses and at the level of an entire country. Pope Francis also recalls synodal processes. In its contributions, this volume aims to deal with individual synods, but also fundamentally with the theological foundations, the development and the juridical structures of these assemblies.